Comparison of Sweated and Non-Sweated Ethanol Extracts of Salvia miltiorrhiza Bge. (Danshen) Effects on Human and Rat Hepatic UDP-Glucuronosyltransferase and Preclinic Herb-Drug Interaction Potential Evaluation - Liu, Jie; Shi, Yun; Wu, Chengyuan; Hong, Bangzhen; Peng, Daiyin; Yu, Nianjun; Wang, Guokai; Wang, Lei; Chen, Weidong (Current Drug Metabolism, 2022)
Background: The ethanol of Danshen (DEE) preparation has been widely used to treat cardiac-cerebral disease and cancer. Sweating is one of the primary processing methods of Danshen, which greatly influences its quality and pharmacological properties. Sweated and non-sweated DEE preparation combined with various synthetic drugs, add up the possibility of herbal-drug interactions. Objective: This study explored the effects of sweated and non-sweated DEE on human and rat hepatic UGT enzyme expression and activity and proposed a potential mechanism. Methods: The expression of two processed DEE on rat UGT1A, UGT2B, and nuclear receptors, including pregnane X receptor (PXR), constitutive androstane receptor (CAR), and peroxisome proliferator-activated receptor α (PPARα), were investigated after intragastric administration in rats by Western blot. Enzyme activity of DEE and its active ingredients (Tanshinone I, Cryptotanshinone, and Tanshinone I) on UGT isoenzymes was evaluated by quantifying probe substrate metabolism and metabolite formation in vitro using Ultra Performance Liquid Chromatography. Results: The two processed DEE (5.40 g/kg) improved UGT1A (P<0.01) and UGT2B (P<0.05) protein expression, and the non-sweated DEE (2.70 g/kg) upregulated UGT2B expression protein (P<0.05), compared with the CMCNa group. On day 28, UGT1A protein expression was increased (P<0.05) both in two processed DEE groups meanwhile, the non-sweated DEE significantly enhanced UGT2B protein expression (P<0.05) on day 21, compared with the CMCNa group. The process underlying this mechanism involved the activation of nuclear receptors CAR, PXR, and PPARα. In vitro, sweated DEE (0-80 μg/mL) significantly inhibited the activity of human UGT1A7 (P<0.05) and rat UGT1A1, 1A8, and 1A9 (P<0.05). Non-sweated DEE (0-80 μg/mL) dramatically suppressed the activity of human UGT1A1, 1A3, 1A6, 1A7, 2B4, and 2B15, and rat UGT1A1, 1A3, 1A7, and 1A9 (P<0.05). Tanshinone I (0-1 μM) inhibited the activity of human UGT1A3, 1A6, and 1A7 (P<0.01) and rat UGT1A3, 1A6, 1A7, and 1A8 (P<0.05). Cryptotanshinone (0-1 μM) remarkably inhibited the activity of human UGT1A3 and 1A7 (P<0.05) and rat UGT1A7, 1A8, and 1A9 (P<0.05). Nonetheless, Tanshinone IIA (0-2 μM) is not a potent UGT inhibitor both in humans and rats. Additionally, there existed significant differences between two processed DEE in the expression of PXR, and the activity of human UGT1A1, 1A3, 1A6, and 2B15 and rat UGT1A3, and 2B15 (P<0.05). Conclusion: The effects of two processed DEE on hepatic UGT enzyme expression and activity differed. Accordingly, the combined usage of related UGTs substrates with DEE and its monomer components preparations may call for caution, depending on the drug’s exposure-response relationship and dose adjustment. Besides, it is vital to pay attention to the distinction between sweated and non-sweated Danshen in clinic, which influences its pharmacological activity.
Keywords: non-sweated